2018
DOI: 10.1016/j.matdes.2017.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Cellular behaviour of bone marrow stromal cells on modified Ti-Nb surfaces

Abstract: The cellular behaviour of bone marrow stromal cells on titanium surfaces modified by niobium diffusion is presented in order to test their osteogenic differentiation response after culturing for 21 days. The surface modification of Ti substrates produced by powder metallurgy was performed through niobium diffusion treatments. Ti-Nb exhibited a β-Ti surface together with a microstructural (β / α+β / α) and compositional (Ti-Nb) gradient which enhances hardness, wear resistance and lowers the elastic modulus mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Similar observations were made in the literature, where it was shown that chitosan/HA coatings increased the surface roughness five times compared to that of the substrate. 45 Recently, Ureña et al 48 showed that the average surface roughness in the range of 1.2–1.5 μm is favorable for the attachment and proliferation of bone marrow stromal cells (ST-2). Therefore, wettability and average roughness of chitosan/AgSr-HA coatings would be better for cells and protein attachment for bone regeneration applications.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Similar observations were made in the literature, where it was shown that chitosan/HA coatings increased the surface roughness five times compared to that of the substrate. 45 Recently, Ureña et al 48 showed that the average surface roughness in the range of 1.2–1.5 μm is favorable for the attachment and proliferation of bone marrow stromal cells (ST-2). Therefore, wettability and average roughness of chitosan/AgSr-HA coatings would be better for cells and protein attachment for bone regeneration applications.…”
Section: Results and Discussionmentioning
confidence: 99%
“…49,50 Furthermore, controlled roughness (R a B 1.3 mm) of the coatings allows the cells to spread over the whole surface. Recently, Ureña et al 51 showed the favorable viability and attachment of ST-2 cells on Ti-Nb surfaces, which were modified to achieve the average roughness in the range of 1.38-1.80 mm. We conclude based on fluorescence microscopy and cell viability test that CGAgMnB coatings persisted and enhanced osteoblastic attachment and proliferation, which could be due to the surface topography, release of ions (dissolution products) from MBGNs and the release of gelatin.…”
Section: Antibacterial Studiesmentioning
confidence: 99%
“…Dry sliding wear of conventional biomedical Ti alloys has been the focus of recent studies, nevertheless there is still relatively little knowledge of the corrosion and tribocorrosion properties of diffusionbased powder metallurgy Ti surfaces designed by thermo-chemical treatments. It is worth emphasizing that these Ti-Nb and Ti-Mo surfaces exhibit improved wear resistance [20] and positive cell-material response [21], [22]. Therefore, is also necessary to study corrosion and tribocorrosion behaviour of these materials before considering them for biomaterials.…”
Section: Introductionmentioning
confidence: 99%